2023
DOI: 10.1002/jmv.28463
|View full text |Cite
|
Sign up to set email alerts
|

The effect of synbiotic adjunct therapy on clinical and paraclinical outcomes in hospitalized COVID‐19 patients: A randomized placebo‐controlled trial

Abstract: Therapeutic approaches with immune-modulatory effects such as probiotics and prebiotics adjuvant therapy may be essential to combat against COVID-19 pandemic. The present trial aimed to reveal the efficacy of synbiotic supplementation on clinical and paraclinical outcomes of hospitalized COVID-19 patients. The current randomized placebo-controlled trial enrolled 78 hospitalized patients with confirmed COVID-19 infection. Participants were randomly allocated to intervention and control groups that received synb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 54 publications
(143 reference statements)
0
25
0
Order By: Relevance
“…Four studies ( 22 , 28 , 29 , 31 ) reported the CRP serum level (mg/L). High heterogeneity was identified using Cochrane's Q test (df = 3, I 2 = 91%, P < 0.00001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies ( 22 , 28 , 29 , 31 ) reported the CRP serum level (mg/L). High heterogeneity was identified using Cochrane's Q test (df = 3, I 2 = 91%, P < 0.00001).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies ( 22 , 25 , 28 , 30 , 31 ) reported the hospital stay (days). A total of 776 patients included, 387 in the probiotics group and 389 in the non-probiotics group.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the inflammatory factor and cognitive status changed significantly, but the cognitive score did not, suggesting a potential benefit of probiotics in immunity regulation. 155 Similarly, Vaezi et al 138 included 78 patients with COVID-19 and randomly administered placebo or synbiotic capsules containing Lactobacillus, Bifidobacterium, and Streptococcus probiotics. After two daily interventions for 14 days, the level of interleukin 6 in the synbiotic supplementation group was significantly reduced.…”
Section: Probiotics Alleviate Uncomfortable Symptoms Of Covid-19mentioning
confidence: 99%
“…After two daily interventions for 14 days, the level of interleukin 6 in the synbiotic supplementation group was significantly reduced. 138 In addition, Catinean et al 156 suggested that patients receiving probiotic supplementation (five strains of bacillus; least one month) may experience faster symptom resolution. Adjunctive therapy of Limosilactobacillus reuteri PBS072 and Bifidobacterium breve BB077 for 30 days improved the quality of sleep and mood, thus reliving stress.…”
Section: Probiotics Alleviate Uncomfortable Symptoms Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation